Energy Governance in South Korea: Long-Term National Energy Master Plans since 1997 - Kim, Dong Young (KDI School of Public Policy and Management, 2020)
Energy, as backbone of economic growth and public welfare, as well as contributor to enhancing or mitigating climate change, is one of the most pressing policy issues for many countries. Overall, national-level energy sector reforms in many countries have been modest without a long-term low-carbon policy framework or coherent set of policies (Gunningham, 2012). It might be due to several characteristics of energy. Energy, as a ‘polycentric’ and ‘mega-issue,’ is inextricably interlinked, vertically and horizontally, with many other sectors and their actors, such as industry, trade, national security, transportation, environment, urban development, and finance (Lesage, Graaf, & Westphal, 2010; Ostrom, 2010). However, energy has been somewhat obscure area left to its own technical experts operating mostly within the conventional realm of energy security and supply (Gunningham, 2012). Governments tend to protect their citizens against energy price fluctuations in fossil fuels or keep energy prices low to earn domestic political support (Dansie, Lanteigne, & Overland, 2010; Goldthau & Sovacool, 2012). Another dimension of energy lies in its path dependency and inertia. Human life and socio-economic activity is so deeply embedded in and dependent on energy that the mutual feedback loop between individual choices and the energy system is reinforced (Goldthau & Sovacool, 2012). Power system, for example, show strong path dependencies of “carbon lock-in” due to the large investments perpetuating a mostly fossil fuel based system of electricity production and consumption (Goldthau & Sovacool, 2012). And alternative options, despite higher performance or lower costs, remain ‘locked-out’ due to vested interests (Markusson & Haszeldine, 2009). Thus, institutional legacies protect status quo (Goldthau & Sovacool, 2012). These challenging characteristics of energy make energy policymaking fragmented and inconsistent with very little coordination between most of relevant actors and make necessary energy reform at most modest. Thus, a daunting but important question is which forms of energy governance (i.e., how to make energy policies with whom) will be more effective in formulating better sustainable energy policies, given expert-oriented and fragmented policy-making and the path dependence and inertia of the prevalent energy systems and their infrastructure, rooted in vested interests of socio-economic entities. Could diverse stakeholders collaborate effectively for sustainable energy policy-making, or necessary energy sector reform? The next chapter discusses briefly two models that explain policy changes through collaboration or conflict: consensus-based regulatory negotiation, and conflict expansion. Then, this paper intends to analyze how governance for national energy policymaking in South Korea (hereafter Korea) has been evolved and to identify which model explains Korean energy governance better. Finally, this paper evaluates current energy governance in Korea and suggests how it should evolve again.